2014
DOI: 10.1099/jmm.0.066738-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromogenic medium and direct latex agglutination test for detection of group B streptococcus in vaginal specimens from pregnant women in Lebanon and Kuwait

Abstract: This study was undertaken to evaluate chromogenic medium and a direct latex agglutination test (DLA) for detection of Group B Streptococcus (GBS) in the vaginal specimens of pregnant women, and to ascertain the prevalence of GBS in this population in Kuwait and Lebanon. Vaginal swabs, collected from women at 35-37 weeks of gestation, were cultured on 5 % sheep blood agar (SBA), colistin nalidixic acid agar (CNA), Strept B Select chromogenic agar (SBS) as well as Lim enrichment broth in 168 cases in Lebanon whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
2
3
1
Order By: Relevance
“…In their study they classified bacterial density quantitatively in contrast to the semiquantitative method in the current study; there may also differences due to LA kit sensitivity and the GBS antigen extraction method between the two studies. Results in the current study are also much lower than those reported by Ghaddar and coworkers 24. On the other hand, many studies proved poor sensitivity and inadequacy of direct GBS antigen detection in vaginal swabs 25…”
Section: Discussioncontrasting
confidence: 82%
“…In their study they classified bacterial density quantitatively in contrast to the semiquantitative method in the current study; there may also differences due to LA kit sensitivity and the GBS antigen extraction method between the two studies. Results in the current study are also much lower than those reported by Ghaddar and coworkers 24. On the other hand, many studies proved poor sensitivity and inadequacy of direct GBS antigen detection in vaginal swabs 25…”
Section: Discussioncontrasting
confidence: 82%
“…Comparison of SBA, CNA and SCB methods revealed that SCB was the most reliable. The sensitivity of CNA was similar to previous reports [ 6 , 9 ] as was the sensitivity of SCB [ 3 ]. SCB is more expensive than SBA or CNA but processing time is reduced.…”
Section: Discussionsupporting
confidence: 90%
“…Hence the test results were dependent on the density of GBS colonization. These result is similar to a comparative study comparing Strept B Select chromogenic agar (SBS) and direct latex agglutination test (DLA) to assure the prevalence of GBS in this population in Kuwait and Lebanon 14 . They found that the sensitivity of the DLA test was found to be dependent on the density of GBS colonization, resulting in 1oo % sensitivity and 1oo % specificity for heavy (>102 c.f.u.…”
Section: Discussionsupporting
confidence: 80%
“…However, for vaginal specimens yielding <50 c.f.u. per swab, the sensitivity, specificity, positive and negative predictive values of the DLA test were 1oo, 55.5, 63.6 and 1oo %, respectively 14 . Thus, we can conclude that SCB can be more accurate than DLA in having the least false negative results.…”
Section: Discussionmentioning
confidence: 92%